(3OjhGf eMeO Hf YHO Gddg Hf TQa GdOjfs - (3eMeO Hf YHO Gddg Hf TQa GdOjf Hf TeS GdOjf Hf GdegOj CMeO Hf jMji,J (B1016 (3g` s ((3GdMSf Hf CMeO GdfUjQ s)
(3ChdgG (B:s
(3ajbhd YjSi Hf dWa Gddg Efi deG aQZJ ef JOhjf eG hLOJg hXaQJ Hg ef TYQ SjOi eMeO Hf YHOGddg GdeYQH , hbVjJ ai Pdc Ojfi , CQOJ Cf CLYd NJGeg GdehTM s
(3BNQgG (B:s
(3ZRGd CMhQ GdYjf , Mhi GdMSf hGdRjf , eTdG GdNO HOjf Je HYhf Gddg GdcQje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ef GdTYQ GdMejfis
(3Ydi ghGeTgG JYdjbGJ s
(3cJHJ GdYfGhjjf HGdMeQI s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs